PENGARUH LINGKUNGAN BELAJAR DI SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA DI SMK NEGERI 1 PONTIANAK - Disty, Fanesa; Nuraini, Nuraini; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe goal of this research was to investigate the extent of the influencebetween the learning environtment at school toward the year-11 students learning motivation at